Veterinary social work: Practice within veterinary settings. Issue 1 (2nd January 2016) - Holcombe, T. Melissa; Strand, Elizabeth B.; Nugent, William R.; Ng, Zenithson Y.
ABSTRACT: Veterinary social work (VSW) is the provision of services at the intersection of veterinary medicine and social work practice. Based on scholarly literature and practice experience, four competency areas are identified for social workers attending to the human side of the human-animal bond: grief at the loss of an animal companion, compassion fatigue in the animal services fields, the connection between animal and human violence, and animal-assisted interventions. This review explores how the four competency areas of VSW have evolved, to what extent these services are being provided, and in what realms these services exist.